2003
DOI: 10.1007/s15010-002-3128-4
|View full text |Cite
|
Sign up to set email alerts
|

Opsonophagocytosis versus Complement Bactericidal Killing as Effectors following Neisseria meningitidis Group C Vaccination

Abstract: PMN did not increase post-vaccination bacterial killing, suggesting that antibody complement-mediated killing, and not opsonophagocytosis, is the main immune effector of the vaccine protection against N. meningitidis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The use of antibiotics as Numbers for each parameter are percentages or median (inter-quartile range). P values were calculated using Chi-square statistic well as booster vaccination is in keeping with previous studies, which have shown that meningococcal vaccination reduces but does not eliminate the risk of meningococcal disease [30] as complement-dependent bacterocidal activity is more important than complement-independent opsonophagocytosis in killing Neisseria meningitidis [31].…”
Section: Discussionmentioning
confidence: 92%
“…The use of antibiotics as Numbers for each parameter are percentages or median (inter-quartile range). P values were calculated using Chi-square statistic well as booster vaccination is in keeping with previous studies, which have shown that meningococcal vaccination reduces but does not eliminate the risk of meningococcal disease [30] as complement-dependent bacterocidal activity is more important than complement-independent opsonophagocytosis in killing Neisseria meningitidis [31].…”
Section: Discussionmentioning
confidence: 92%
“…The OPA can be semi-automated and use beads coated with capsular polysaccharide and can also be multiplexed to analyze four serogroups in the one assay [64]. A recent study has suggested that SBA is the main immune effector of the vaccine protection against N. meningitidis rather than opsonophagocytosis following serogroup C vaccination [68]. Furthermore, there are issues of standardization between laboratories, particularly regarding the use of cultured cell lines or freshly obtained PMN cells.…”
Section: Additional Correlates Of Protectionmentioning
confidence: 99%